2005
DOI: 10.1111/j.1365-2966.2005.09573.x
|View full text |Cite
|
Sign up to set email alerts
|

Candidate extrasolar planet transits discovered in the Microlensing Observations in Astrophysics-I Galactic bulge data

Abstract: We present the results of a search for candidate planetary transits using the Microlensing Observations in Astrophysics‐I (MOA‐I) microlensing survey data in the Galactic bulge. To achieve sufficient photometric precision, the analysis was confined to a selected subset of stars on selected images. Periodicities of light curves were found with a Box fitting Least Squares (BLS) procedure. This yielded 12 candidates. The derived radii of the candidates ranged from 1.7 to 3.2 RJ, consistent with interpretations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…In 1998, the camera was upgraded to MOA-cam2 which consists of three 2k×4k CCD SITe ST-002A chips. The details of MOA-cam2 are described by Yanagisawa et al [12] Mainly using MOA-cam2, MOA has successfully detected microlensing events [13], and also from the mass photometry database, MOA has studied variable stars [14,15]. MOA has also succeeded in establishing a rapid alert system for microlensing candidates [7] (http://www.massey.ac.nz/~iabond/alert/alert.html).…”
Section: Moamentioning
confidence: 99%
“…In 1998, the camera was upgraded to MOA-cam2 which consists of three 2k×4k CCD SITe ST-002A chips. The details of MOA-cam2 are described by Yanagisawa et al [12] Mainly using MOA-cam2, MOA has successfully detected microlensing events [13], and also from the mass photometry database, MOA has studied variable stars [14,15]. MOA has also succeeded in establishing a rapid alert system for microlensing candidates [7] (http://www.massey.ac.nz/~iabond/alert/alert.html).…”
Section: Moamentioning
confidence: 99%
“…Hood et al (2005) observed NGC 6940 using the 2.5 m Isaac Newton Telescope with its Wide Field Camera, a mosaic consisting of four 2048 × 4096 pixels CCDs. The MOA-I project observed 14 Galactic Bulge fields using the 61 cm Boller and Chivens Telescope at the Mt.John University Observatory with three 2048 × 4096 pixels CCDs (Abe et al 2005). SuperWASP (Christian et al 2004), Vulcan (Borucki et al 2001), and others are also conducting very wide-field transit surveys similar to TrEs.…”
Section: Introductionmentioning
confidence: 99%